2020
DOI: 10.30813/bricolage.v6i01.2067
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Strategi Digital Marketing Communication Bagi Industri Perhotelan Dalam Menjawab Tantangan Era Posmodern

Abstract: The development of consumer culture in the era of technology has a direct impact on business competition in the hospitality sector. To be in a superior position in winning the competition, it requires the implementation of strategic planning. With the significant growth of internet users, the hotel industry must make good use of the situation, namely promoting digital marketing communication strategies. The purpose of this research is to design a digital marketing communication strategy for the Golden Tulip Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
6
0
7
Order By: Relevance
“…Dengan smart digital content marketing pengusaha dapat dengan mudah mendapatkan konsumen dari kalangan milenial (Hayu, 2019). Perkembangan budaya konsumen di era teknologi yang semakin canggih ini berdampak langsung pada bisnis atau dunia usaha (Teguh & Ciawati, 2020).…”
Section: A Pendahuluanunclassified
“…Dengan smart digital content marketing pengusaha dapat dengan mudah mendapatkan konsumen dari kalangan milenial (Hayu, 2019). Perkembangan budaya konsumen di era teknologi yang semakin canggih ini berdampak langsung pada bisnis atau dunia usaha (Teguh & Ciawati, 2020).…”
Section: A Pendahuluanunclassified
“…Contoh-contoh kegiatannya antara lain pemasaran melalui website, pemasaran melalui media sosial, optimasi mesin pencari, pemasaran pada aplikasi mobile, dan sebagainya. Terdapat beberapa keunggulan utama dari kegiatan promosi ini yaitu ruang lingkup atau jangkauan yang luas, tidak terbatas oleh waktu dan lokasi geografis, serta dapat menarget langsung pelanggan potensial (Teguh & Ciawati, 2020).…”
Section: Digital Marketingunclassified
“…This area for improvement on lack of social media and website updates regarding tourism destinations by North Sulawesi Provincial Government was confirmed during in-depth interviews with a local mass media editor and a tourism college lecturer. A study focusing on the website and Instagram design as the primary access to information distribution of a legacy hotel in Surabaya indicated that the design of innovative digital marketing communication strategies could be made with a management calendar, content formulation system, updated website features, optimised Instagram and following the Teguh & Ciawati (2020). Indonesia, as the biggest of Social Media user on Southeast Asia, has been rapidly changing on Social Media Platform.…”
Section: Regional Tourism Brandingmentioning
confidence: 99%